(untitled) (Bangladesh Journal of Medical Science, 2018)
In Pakistan the effect population mobility, specifically labor migration and refugees is also thought to have been important in explaining the rapid spread of HIV/AIDS. One of the effects labor migration is likely to have had increased the prevalence of the overlap of sexual partnership. A nonlinear fractional differential equation model is discussed for transmission and control of HIV/AIDS in Pakistan. We shall also discuss the disease free equilibrium and stability behavior of the model Bangladesh Journal of Medical Science Vol.18(1) 2019 p.14-23